Indian cereal crops (wheat and rice) phenology and agricultural management data across Indian croplands from 1960 extquotesingles to 2020 - Gudimetla Venkateswara Varma; Kangari Narender Reddy; Somnath Baidya Roy; Riya Yadav; Gayatri Vangala; Ruchira Biswas (PANGAEA, 2024)
The site scale observations of the Indian crops are very rarely available for public access. Students at all agricultural institutes across India carry out experiments on Indian crops as part of their curriculum and report the results in a thesis. The thesis from such institutes is uploaded to the Krishikosh repository (https://krishikosh.egranth.ac.in). To fill the gap of absence of crop data on Indian crops, we started to look at this repository and collect data. We have collected and harmonized crop phenology and agricultural management data of major Indian crops such as spring wheat and rice from these theses. This dataset is the first of its kind, providing and combining weather data from several crop-growing regions. We are combining data from 83 theses related to rice and data from 64 theses related to spring wheat. These data are from 48 individual sites, a few of which have multiple growing seasons.